Pyoderma Gangrenosum Mimicking an Infected Wound following Dynamic Hip Screw Fixation - Metin Nizamoglu (Case Reports in Orthopedics)
Pyoderma gangrenosum (PG) is an inflammatory ulcerative neutrophilic dermatosis that can occur following skin trauma. The correct diagnosis is not often made immediately as the condition can mimic an infective appearance. This leads to delays in the appropriate management of high dose steroids. Although debridement can offer aid in resolving lesions, this is contraindicated in the acute phase as this can cause acceleration of the pathogenic process. Biopsy of the lesion does not offer a definitive diagnosis; therefore suspicion must be maintained as the diagnosis is ultimately a clinical one. Any postoperative pustular ulcerative lesion not improving despite antibiotic therapy that also yields negative bacteriological and fungal studies should lead to consideration of this diagnosis. We document the first case of PG developing following intertrochanteric femur fracture fixation using dynamic hip screw.